Tragedy of the Partnership: A Critique of Elinor Ostrom. (March 2016) - Block, Walter; Jankovic, Ivan
Abstract: Elinor Ostrom thinks she has discovered a third way apart from private and government property: the commons. In her view, there is no "tragedy" associated with this third option. The present article takes strong issue with her. Our claim is that she has not properly distinguished between a commons and partnership arrangements. In the former case, outsiders cannot be excluded from entry; in the latter, they can. The reason for this confusion between the commons and private property in Ostrom's work is that she believes private property is possible only if government protects and enforces it. We show by using various historical examples that this assumption is wrong, and hence the central tenet of Ostrom's model of the commons fails.